EDU707 : Quantitative research methods and analysis / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
The purpose of this course is to provide students with an introduction to many different types of quantitative research methods and statistical techniques. This course will be divided into two major sections: 1) methods for quantitative research and, 2) quantitative statistical techniques for analysing data. Throughout the course, students will gain an overview of the important concepts of research design, data collection, statistical and interpretative analysis, and final report presentation. Major areas to be discuss in the research methods include research designs, sampling, instrumentation and validation process whereas for the statistical techniques will include descriptive and inferential statistics and applications of SPSS as a tool in assisting data analysis and interpretation. For this statistical analysis section, greater emphasis will be placed on interpretation and understanding of concepts rather than computation.